Appeal of novel cessation intervention approaches among young-adult users of traditional and alternative tobacco products. (4th October 2021) - Berg, Carla J; Romm, Katelyn F; Patterson, Brooke; Wysota, Christina; Abroms, Lorien C
Significance: Given limited research on young-adult tobacco cessation interventions, we examined preferred tobacco/e-cigarette cessation approaches among young-adult tobacco/e-cigarette users. Methods: We analyzed Spring 2020 data from a longitudinal study of young adults (ages 18–34) across 6 metropolitan areas (Atlanta, Boston, Minneapolis, Oklahoma City, San Diego, and Seattle). We examined tobacco/e-cigarette use and self-reported appeal of various intervention approaches, and regarding technology-based approaches, the appeal of types of technology and intervention functions. Results: In this sample of past 6-month tobacco/e-cigarette users (Mage = 24.69; 48.4% male; 73.3% White), 59.6% used e-cigarettes, and 48.2% used cigarettes. The most frequently endorsed intervention approach was nicotine replacement therapy (NRT; 72.7%), followed by technology-based programs (70.0%) and oral medications (53.0%). The most frequently endorsed technology-based approach was smartphone apps (85.9%), followed by programs involving text-messaging (62.1%), websites (57.1%), social media (48.4%), and video counseling (41.6%). The most frequently endorsed technology-based program function was behavioral monitoring (68.3%), followed by earning rewards (60.3%). We identified no differences in approach appeal among subcategories of tobacco/e-cigarette users. Conclusions: Findings underscore the promise of technology-based approaches, particularly apps, and text-messaging for tobacco/e-cigarette cessation, and functions like behavioral monitoring and gamification. Additionally, appropriate and effective NRT use for young-adult tobacco/e-cigarette users warrants further research.